Cześć ;-)
a)
[tex](2x^2-3x-4)+(x^2+3x-2)=\\\\=2x^2-3x-4+x^2+3x-2=\\\\=2x^2+x^2-3x+3x-4-2=\boxed{3x^2-6}[/tex]
b)
[tex]-(3x+2y)+(4x-5y)=\\\\=-3x-2y+4x-5y=\\\\=-3x+4x-2y-5y=\boxed{x-7y}[/tex]
c)
[tex](5x^3-6x^2-5x+4)-(2x^3-4x^2+2x-4)=\\\\=5x^3-6x^2-5x+4-2x^3+4x^2-2x+4=\\\\=5x^3-2x^3-6x^2+4x^2-5x-2x+4+4=\boxed{3x^3-2x^2-7x+8}[/tex]
d)
[tex](2a+3b-4c)-(3a-2b+2c)-(-a-5b-6c)=\\\\=2a+3b-4c-3a+2b-2c+a+5b+6c=\\\\=2a-3a+a+3b+2b+5b-4c-2c+6c=\boxed{10b}[/tex]
e)
[tex]-(4x^2+3)+(2x^2-6x+2)-(x^2-8x-1)=\\\\=-4x^2-3+2x^2-6x+2-x^2+8x+1=\\\\=-4x^2+2x^2-6x+8x-3+2+1=\boxed{-2x^2+2x}[/tex]
f)
[tex](5x^5+2x^4-3x^3+2x^2+3x+2)-(4x^5-3x^4+2x^3+5x^2-3x-1)=\\\\=5x^5+2x^4-3x^3+2x^2+3x+2-4x^5+3x^4-2x^3-5x^2+3x+1=\\\\=5x^5-4x^5+2x^4+3x^4-3x^3-2x^3+2x^2-5x^2+3x+3x+2+1=\\\\=\boxed{x^5+5x^4-5x^3-3x^2+6x+3}[/tex]
Pozdrawiam!